1997
DOI: 10.2172/663557
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of metallic substrate composition on degradation of thermal barrier coatings

Abstract: 6%Comparisons have been made in laboratory isothermal and cyclic oxidation tests of the degradation of oxide scales grown on single crystal superalloy substrates and bond coating alloys intended for use in thermal barrier coatings systems. The influence of desulphurisation of the superalloy and bond coating, of reactive element addition to the bond coating alloy, and of oxidation temperature on the spallation behavior of the alumina scales formed was assessed from oxidation kinetics and from SEM observations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…After a 100h isothermal exposure at 1100°C, this layer was ≈ 500nm thick and contained Ni, Co, Cr and Al, Figure 6. At the transient oxide-alumina interface, numerous Ta-rich oxide particles were observed, as has been noted previously [9,29]. The underlying alumina layer showed no defects and was similar to that formed on NiCrAlY except that the column width (≈ 0.3µm average) was somewhat smaller than that on NiCrAlY (≈ 0.4µm average).…”
Section: Nicralysupporting
confidence: 77%
“…After a 100h isothermal exposure at 1100°C, this layer was ≈ 500nm thick and contained Ni, Co, Cr and Al, Figure 6. At the transient oxide-alumina interface, numerous Ta-rich oxide particles were observed, as has been noted previously [9,29]. The underlying alumina layer showed no defects and was similar to that formed on NiCrAlY except that the column width (≈ 0.3µm average) was somewhat smaller than that on NiCrAlY (≈ 0.4µm average).…”
Section: Nicralysupporting
confidence: 77%
“…However, beneficial effects of reactive element additions. [11,32] even with a relatively high sulfur content, (Ni, Pt)Al coatings The nonplanar geometry of the grain boundary ridges may showed superior scale adhesion after 200 cycles at 1150 ЊC. also play an important role in accelerating failure at these In fact, very little spallation was observed at the (Ni, Pt)Al sites.…”
Section: Methodsmentioning
confidence: 99%
“…The additional depletion of the matrix by Al (and Fe) by the formation of Al 2 O 3 and Fe 2 O 3 may further support the formation of Laves phase. For Ni-base superalloys it has been shown that Ta diffuses outwards to the metal/oxide scale interface where then Ta-rich phases e in that case probably carbides e form [23,24]. It is assumed that, like in the case of other elements, the oxygen potential gradient is the driving force for the outward diffusion of Ta [23,25].…”
Section: Oxidation Behaviour Of Fee25ale2ta and Comparison To Other Tmentioning
confidence: 99%
“…Also from Ni-base superalloys it is known that the formation of Ta-rich particles at the metal/scale interface leads to spallation of the scales [23,24]. One mechanism that leads to spallation is that Tarich particles at the sample surface are undercut by the growing scale which cracks at the particle/oxide interface during cooling [24]. This mechanism seems not to be responsible for the spallation of the present scales because the Laves phase particles are not undercut by the growing scale and are still on the sample surface after the scale spalled (Figs.…”
Section: Oxidation Behaviour Of Fee25ale2ta and Comparison To Other Tmentioning
confidence: 99%